Association of subclinical atherosclerosis and cognitive decline: a community-based cross-sectional study. Issue 5 (24th May 2022) - Lu, Yao; Zhu, Yidan; Ma, Yanjun; Li, Chenglong; Hua, Rong; Zhong, Baoliang; Wang, Hongyu; Xie, Wuxiang
Abstract : Background and aims: Growing burden of dementia was considered as a global public health priority as its epidemic scale rises with the world's population increases in age. In the absence of effective treatment, early identification of decline in cognitive function and risk factors that lead to the onset of dementia is a critical issue. Subclinical atherosclerosis may be a potential risk factor for cognitive impairment and progression to dementia. Research is needed to identify which subclinical atherosclerosis risk factors can better predict cognitive decline. Methods: A total of 1554 participants (mean age 59.81±6.93 years) were enrolled from Beijing Research on Ageing and Vessel and underwent baseline evaluation. Carotid intima-media thickness, carotid plaque and brachial ankle pulse wave velocity (ba-PWV) were selected as subclinical atherosclerosis markers. Cognitive function assessment was conducted by standardised tasks to assess the associations with subclinical atherosclerosis markers. Results: Significant associations (p<0.001) were shown in the unadjusted models between all three subclinical atherosclerosis markers and cognitive function assessments. After adjusting for covariates, in the assessment of the association between carotid atherosclerosis and cognitive function, plaque numbers showed signiﬁcant associations in Montreal Cognitive Assessment (MoCA) (β=−0.15, p=0.006) and verbal memory scores (β=−0.13, p=0.013). While in the assessment of the association between arterial stiffness and cognitive function, ba-PWV showed signiﬁcant associations in MoCA (β=−0.09, p=0.009) and semantic fluency scores (β=−0.13, p=0.036). Conclusions: Positive associations shown between subclinical atherosclerosis and cognitive function. Subclinical atherosclerosis markers of plaque numbers were significantly associated with global cognitive functioning in MoCA, memory and semantic fluency, while ba-PWV was significantly associated with global cognitive functioning in MoCA and semantic fluency.